2020
DOI: 10.1159/000506622
|View full text |Cite
|
Sign up to set email alerts
|

Protroca: A Noninterventional Study on Prophylactic Lipegfilgrastim against Chemotherapy-Induced Neutropenia in Nonselected Breast Cancer Patients

Abstract: <b><i>Background:</i></b> Protroca evaluated the efficacy and safety of primary and secondary prophylaxis of neutropenia with lipegfilgrastim (Lonquex®) in breast cancer patients receiving neoadjuvant or adjuvant chemotherapy (CT). <b><i>Patients and Methods:</i></b> Of the 255 patients enrolled, 248 patients were evaluable for the intent-to-treat (ITT) and 194 patients for the per-protocol set. Primary and secondary end points after lipegfilgrastim treatment wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(19 reference statements)
1
1
0
Order By: Relevance
“…The incidence of chemotherapy delays in a cycle was higher than in the phase III study (the highest 22.6% vs. 16.2%) (data not shown), and longer was the average delay across all cycles (median 7.0 [range, 1.0 to 77.0] vs. 0.0 [0.0 to 14.0] days) [10]. In the Protroca study, assessing the effectiveness and safety of lipegfilgrastim in non-selected breast cancer patients the incidence of delay of chemotherapy was similar to our study [11]. Timmer-Bonte et al reported higher rates of delay, but their study included also the patients with haematological malignancies and solid tumours other than breast cancer [12].…”
Section: Discussionsupporting
confidence: 83%
“…The incidence of chemotherapy delays in a cycle was higher than in the phase III study (the highest 22.6% vs. 16.2%) (data not shown), and longer was the average delay across all cycles (median 7.0 [range, 1.0 to 77.0] vs. 0.0 [0.0 to 14.0] days) [10]. In the Protroca study, assessing the effectiveness and safety of lipegfilgrastim in non-selected breast cancer patients the incidence of delay of chemotherapy was similar to our study [11]. Timmer-Bonte et al reported higher rates of delay, but their study included also the patients with haematological malignancies and solid tumours other than breast cancer [12].…”
Section: Discussionsupporting
confidence: 83%
“…The higher FN rate within NADENS may be due to the more intense CTx regimen applied, the unselected patient population, and/or the prophylactic use of systemically active antibiotics in one RCT for patients at high risk for infection [20]. A recently published real-world study in BC patients (Protroca) showed for the subgroup of patients with primary prophylaxis comparable results: the observed rate of FN across up to 4 cycles of CTx is 2.25% versus 2.1% in NADENS [21]. SN was experienced in 33.3% of patients during the first dd cycle and in 46.5% of patients during the entire 4 documented dd cycles in NADENS.…”
Section: Discussionmentioning
confidence: 99%